1987
DOI: 10.1002/kin.550190302
|View full text |Cite
|
Sign up to set email alerts
|

On the errors of Arrhenius parameters and estimated rate constant values

Abstract: A detailed statistical study is presented, based on simulated experimental data, on the estimation of activation parameters using the Arrhenius equation: k = A exp!B/T).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 8 publications
1
46
1
1
Order By: Relevance
“…First, if the relative weights (ratios) are statistical or instrumental, the magnitudes of the deviations should reflect the experimental errors. When this is true, the value of the reduced chi-squared, 2 divided by the number of degrees of freedom, will be near unity. In this situation, the deviations are said to be internally consistent and they may be used without modification.…”
Section: Chi-squared Minimizationmentioning
confidence: 95%
See 2 more Smart Citations
“…First, if the relative weights (ratios) are statistical or instrumental, the magnitudes of the deviations should reflect the experimental errors. When this is true, the value of the reduced chi-squared, 2 divided by the number of degrees of freedom, will be near unity. In this situation, the deviations are said to be internally consistent and they may be used without modification.…”
Section: Chi-squared Minimizationmentioning
confidence: 95%
“…After experiments have been performed, the best-fit values of the independent parameters are generally determined by minimizing the chi-squared merit function, 2 (a), defined by…”
Section: Chi-squared Minimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established but rarely acknowledged that uncertainties on paired Arrhenius parameters are highly correlated (Héberger and Kemény, 1987;Nagy and Turányi, 2011). Since such correlations have direct bearing on the application of carbonate ∆47 reordering models (e.g., Lloyd et al, 2017), it is worth considering how the families of dolomite ∆47 reordering parameters covary here.…”
Section: The Transient Defect/equilibrium Defect Modelmentioning
confidence: 99%
“…The uncertainties of Arrhenius parameters have also been investigated by Héberger et al [4]. They concluded that the Arrhenius coefficients determined in most experiments are highly correlated and that this correlation should be characterized by a covariance matrix.…”
Section: Introductionmentioning
confidence: 97%